2020
DOI: 10.3390/ijms21124356
|View full text |Cite
|
Sign up to set email alerts
|

GLI1 and AXIN2 Are Distinctive Markers of Human Calvarial Mesenchymal Stromal Cells in Nonsyndromic Craniosynostosis

Abstract: All skeletal bones house osteogenic stem cell niches, in which mesenchymal stromal cells (MSC) provide progenitors for tissue growth and regeneration. They have been widely studied in long bones formed through endochondral ossification. Limited information is available on the composition of the osteogenic niche in flat bones (i.e., skull vault bones) that develop through direct membranous ossification. Craniosynostosis (CS) is a congenital craniofacial defect due to the excessive and premature ossification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…They also showed that the implantation of MSC-graft leads to suture regeneration by restoring Gli1 + cells subpopulation within cranial suture both through exogenously implanted Gli1+ MSCs and endogenous MSCs derived from the dura mater [108]. Our group has indeed recently demonstrated that GLI1 represents a specific marker for MSC in the human calvarial niche [21].…”
Section: Tissue Engineering Strategiesmentioning
confidence: 85%
See 2 more Smart Citations
“…They also showed that the implantation of MSC-graft leads to suture regeneration by restoring Gli1 + cells subpopulation within cranial suture both through exogenously implanted Gli1+ MSCs and endogenous MSCs derived from the dura mater [108]. Our group has indeed recently demonstrated that GLI1 represents a specific marker for MSC in the human calvarial niche [21].…”
Section: Tissue Engineering Strategiesmentioning
confidence: 85%
“…The suture mesenchyme represents a unique skeletogenic stem cell niche in the developing skull, serving as a transient reservoir of mesenchymal stromal cells (MSC) and osteoprogenitors (see Figure 1) [21,22]. Regardless of the initial trigger underlying CS etiology, it is believed that in these disorders the calvarial suture stem cell niche undergoes an accelerated exhaustion, which ultimately drives the premature ossification of the suture mesenchyme [20,23].…”
Section: Craniosynostosis: a Heterogeneous Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once closed, sutures appear to lose their MSC population. The Gli1+ population is lost at the site of the fused interfrontal suture in mice ( Zhao et al, 2015 ), whilst there is a reduction in the Axin2 population at prematurely fused sutures in craniosynostosis patients ( Di Pietro et al, 2020 ). Thus, suggesting that an open suture status is necessary for the suture to contain a reservoir of MSCs enabling it to function as a site of interstitial bone growth and support normal craniofacial development.…”
Section: The Importance Of Suturesmentioning
confidence: 99%
“…Marsupials exhibit a lower level of closure than placentals, and sutures are reported to remain open throughout life ( Rager et al, 2014 ). It is thus possible that variation in suture closure between placentals and marsupials may be indicative of differing postnatal functional roles, especially given the significance of suture fusion status in supporting postcranial bone growth ( Zhao et al, 2015 ; Di Pietro et al, 2020 ).…”
Section: The Importance Of Suturesmentioning
confidence: 99%